Four-quadrant modelling of carbon inequality in international trade and accounting for carbon compensation - Hao Chen; Erdan Wang; Tao Song; Yu Wang; Zulin Ye (Carbon Management)
In global trade, there is a phenomenon that the “economic gains” and “ecological damages” of some countries and regions are not consistent. Using the multi-regional input-output model (MRIO), this study measures the transfer of embodied carbon and value-added in trade among 16 countries or regions, including the European Union, the United States and other countries from 1995 to 2022. On this basis, we use the four-quadrant analysis method to classify the carbon inequality in international trade, and construct the carbon inequality index to quantify the carbon inequality situation in bilateral trade. The results indicate that carbon inequality between international trade can be divided into three categories: victims of absolute carbon inequality, relative carbon equality and beneficiaries of absolute carbon inequality. Carbon inequality in bilateral trade exists between developed and developing countries, as well as between developing countries. Finally, a carbon compensation accounting model is constructed to measure the monetary value of cross-regional carbon offset, which provides data support for international carbon emission reduction cooperation. Our study contributes to contemplating the impacts of international trade and provide recommendations for global equity and sustainable development.